A TVA to the Amazon forest? Shaping experts for development - Andrade, Rômulo de Paula (Diálogos Latinoamericanos, 2022)
This article aims to analyze the courses of the Superintendência de Valorização Econômica da Amazônia (SPVEA), the government agency responsible for development projects in the Brazilian Amazon. In the 1950s, SPVEA held courses for the technical experts that were going implement the region’s development plans. Amidst several intervention projects in the Amazon Forest, the teaching of modern planning techniques intended to award technical status to the actions taken and to remove political influence from the plans. The sources used in this paper are the syllabi of the courses held at Fundação Getúlio Vargas in the 1950s for future SPVEA workers as well as reports, books and advertising materials published by the agency itself. Through these historical sources, it will be possible to perceive the reception and adaptation of planning and development ideas that circulated in Brazil during the Cold War.